How does pole length affect lower back muscle activity at different inclines and skiing intensities during double poling? - Lund Ohlsson, M.; Nilsson, M.; Swarén, M. (Frontiers in Sports and Active Living, 2025)
Purpose: This study aimed to investigate how pole length, incline, and skiing intensity affect lower back muscle activation in elite cross-country skiers. This addressing a critical gap in understanding the biomechanical demands and risk of low back pain of double poling (DP).